A study of RNA splicing and protein expression in the living human brain - Brian H. Kopell; Deepak A. Kaji; Lora E. Liharska; Eric Vornholt; Anina Lund; Alice Hashemi; Ryan C. Thompson; Jessica S. Johnson; Nicole Bussola; Esther Cheng; You Jeong Park; Punit Shah; et al. (PLoS ONE, 2025)
Due to the unavailability of living human brain tissue for molecular research, postmortem brain samples are currently the standard tissue source for molecular studies of the human brain. The Living Brain Project (LBP) was designed to test the assumption that the postmortem brain is an accurate molecular representation of in the living brain on multiple levels of molecular biology. Findings from previous LBP reports suggest that this assumption does not hold with respect to RNA transcript expression levels. Here, molecular differences between living and postmortem human prefrontal cortex tissues obtained for the LBP are corroborated through analyses of RNA splicing and protein expression data. Significant differences were observed with respect to (1) the expression of most primary RNA transcripts, mature RNA transcripts, and proteins, (2) the splicing of most primary RNA transcripts into mature RNA transcripts, and (3) the patterns of co-expression between RNA transcripts and proteins. Taken together, this report corroborates the presence of widespread molecular differences between living and postmortem human brain tissues. These observations should be considered when designing and interpreting studies of human brain biology.